Directing Between the Lines: Iranian Theatre and the Aesthetics of Ambiguity - Mirsajadi, Ali-Reza. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Drama.; Advisor: Noe Montez.; Committee: Heather Nathans, Kamran Rastegar, and Sheida Dayani.; Keywords: Theater history, Middle Eastern studies, and Gender studies.